EFEKTIVITAS EKSTRAK KULIT BATANG, AKAR, DAN DAUN SIRSAK (Annona muricata L) TERHADAP KADAR GLUKOSA DARAH - Siti Rahmawati; Najda Rifqiyati (Kaunia: Integration and Interconnection Islam and Science, 2014)
Sour-sop is known for its specialty for health, in which one of them is functioning as medicine for diabetes mellitus disease. However, most people only utilize its leaves. This research is aimed at defining effectiveness of extracts of barks, roots, and leaves in decreasing blood glucose level as well as observing the most effective part in decreasing blood glucose level. Applied methods include completely random method by using 15 mice divided into 5 groups, namely K-, K+, P1, P2, and P3. Groups K+, P1, P2, P3 were injected with STZ at dosage of 40 mg/kg. Group K- was only provided with aquades, K+ was given metformin at dosage of 60 mg/kg BB, while groups P1, P2, and P3 were given extracts of bark, roots, and leaves at dosage of 125 mg/kg BW, respectively. Glucose level Measuements were conducted twice, namely fasting blood glucose level and blood glucose 2 hours after eating. Obtained data was then analyzed using ANOVA one way test and then continued by using LSD test. For measurement of fasting blood glucose level in day 15 after treatment, results for level of fasting blood glucose of K- ( 88 mg/dl), K+ (234 mg/dl), P1 (93 mg/dl), P2 (397 mg/dl), and P3 (254,67 mg/dl). Whereas for measurement of blood glucose level after 2 hours of eating, results for K- (116.67 mg/dl), K+ (562 mg/dl), P1 (561.67 mg/dl), P2 (498.3 mg/dl), and P3 (489 mg/dl). Obtained result of Anova one way shows that there is difference in glucose level among different treatments. For LSD test, it was found that for measurement of fasting blood glucose level for P1 and K-, there is no different level of glucose but difference was found at treatment taken 2 hours after eating. Whereas for K+, P2, and P3, difference was found between fasting blood glucose level and that taken 2 hours after eating. P1 (extract of bark) effectively decreased level of fasting blood glucose but did not yet effectively reduce level of blood glucose 2 hours after eating; whereas P2 and P3 did not effectively  educe levels of fasting blood glucose and blood glucose 2 hours after eating. Bark is the most effective part in reducing blood glucose level.